2018
DOI: 10.3329/bhj.v33i2.39310
|View full text |Cite
|
Sign up to set email alerts
|

Brachio- Axillary Translocation Fistula with Reverse Saphenous Venous Graft: a New Hope for the Patients of End stage Renal Disease

Abstract: Native arterio-venous fistula (AVF) are the preferred mode of repeated vascular access for the chronic renal failure patients surviving on hemodialysis because of their easy accessibility, good long term patency, low complication rate and cost-effectiveness. Creation of a fistula between the radial or brachial artery and a suitable adjacent vein is the most commonly practiced option. However the major upper arm veins of the CKD patients are often found thrombosed, cord like and not suitable for AV anastomosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…They concluded that the combined block provides good anaesthesia for the entire right upper limb, and explained that SCB is a reliable technique giving anaesthesia for the distal arm and ISB increased the remaining quality of the motor and sensory blockade. 16 In our study, we observed significant decrease in NRS in RA group during the 24 hour postoperative period that compares with Gebhard et al who reported the advantage of postoperative analgesia after regional anaesthesia. 17 The significant reduction in frequency of analgesia requirement and the longer duration of the first need of analgesia in RA group could be explained by excellent analgesia of both blocks.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…They concluded that the combined block provides good anaesthesia for the entire right upper limb, and explained that SCB is a reliable technique giving anaesthesia for the distal arm and ISB increased the remaining quality of the motor and sensory blockade. 16 In our study, we observed significant decrease in NRS in RA group during the 24 hour postoperative period that compares with Gebhard et al who reported the advantage of postoperative analgesia after regional anaesthesia. 17 The significant reduction in frequency of analgesia requirement and the longer duration of the first need of analgesia in RA group could be explained by excellent analgesia of both blocks.…”
Section: Discussionsupporting
confidence: 68%
“…20 To our knowledge, only few studies have discussed combined SCB and ISBusage. 1,16,20 Our study is the first to describe this combined block in patients with CRF.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation